Advanced colonoscopic imaging using endocytoscopy - Neumann, Helmut; Kudo, Shin-Ei; Kiesslich, Ralf; Neurath, Markus (Digestive Endoscopy, 2015)
Optical biopsy techniques were recently introduced to luminal gastrointestinal endoscopy. These include confocal laser endomicroscopy, spectroscopic imaging techniques and endocytoscopy. Optical biopsy techniques allow on demand in vivo histology during ongoing endoscopy, thereby potentially accelerating clinical diagnosis and specific therapy. In the present review, we focus on endocytoscopy as one of the rapidly emerging optical biopsy techniques. We provide technical details of currently available endocytoscopy systems and give tips on their use in clinical practice. We also summarize applications of endocytoscopy for colorectal pathologies.
EVALuna2:2024